The projects of lija Kabakow. Life in a space time installation - López Farjeat, Luis Xavier (Estudios de Filosofía, 2000)
This paper diagnoses Contemporary art and analyses the art of installation based on the works and ideas of lija Kabakow. The purpose is to illustrate that artistic activity is far from being exhausted. On the contrary, new techniques and styles open a quite wide horizon of concepts, confirming that art is an autonomous language with countless possibilities of expression.